Large thyroglossal duct cyst with a long term evolution: a case report - Serrano-Trejo, Isabel; Luna-Peteuil, Zelik; Naranjo-Gonzalez, Ana C.; Luna-Ortiz, Kuauhyama (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2024)
A 57-year-old male presented with a progressively enlarging mass in the anterior cervical region, persisting for 41 years without accompanying symptoms. Physical examination revealed a well-defined, mobile, soft mass measuring 16×15×15 cm, not fixed to deep tissues, and extending from the medial edge of the sternocleidomastoid muscle. Computed tomography scan showed a cystic lesion involving the hyoid bone, suggestive of a thyroglossal duct cyst. The patient underwent a Sistrunk procedure, with dissection from the base of the tongue to the sternal notch. He was discharged six hours after surgery without any complications and had a closed drainage system removed during a subsequent outpatient visit.